THE POTENTIAL BENEFIT AND THE MECHANISM OF ACTION OF THYROXINE ON SERUM LIPIDS AND BLOOD FLOW INDEXES IN SUBCLINICAL HYPOTHYROIDISM WOMEN - Kadhim, Sinaaabdul Amir; Kadhum, Shaimaa Abdul Ameer; Hamza, Ali Jawad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Even previous reports mentioned that thyroxine has beneficial effects on subclinical hypothyroidism (SCH); however, the mechanism by which thyroxine mediated such effect still unclear. Thus, we aim to find out the potential benefit of thyroxine administration in women with SCH through assessment of lipids profile with evaluation of uterine and ovarian blood flow indexes. Methods: The current study included 80 women with SCH who had a history of recurrent intrauterine death. Those women were chosen from the cohort of pregnant ladies that routinely seek medical advice. For each woman, estimation of serum thyroid-stimulating hormone (TSH), serum lipids profile (low-density lipoprotein [LDL], total cholesterol [TC], and triglyceride [TG]), and also uterine and ovarian pulsatile index (PI) and resistance index (RI) using color Doppler ultrasound, was done at the beginning of study and then repeated following 2 months during which women were given oral thyroxine supplementation (50 Î¼g/d). The study was carried out in Al-Diwaniyah Maternity and Child Teaching Hospital in Al-Diwaniyah province, Iraq and extended from September 2016 to January 2018. Results: Mean serum TSH, LDL, TG, and TC were significantly reduced (p<0.05). Mean early follicular phase ovarian RI and PI and uterine RI were significantly reduced (p<0.05). In addition, mean late follicular phase ovarian RI and PI and uterine RI were significantly reduced (p<0.05). Conclusion: Thyroxine administration to women with SCH significantly decreases serum lipids and increases uterine and ovarian blood flow by mechanism involving reduction in arterial RI and PI.